Development Of Network Security Systems Using Computer-Based Encryption And Authentication Techniques - Firdaus (Riset Sinergi Indonesia (RISINDO), 2024)
Network security has become a critical issue in today's digital era, given the numerous threats that can compromise the integrity and confidentiality of data. One approach to address this problem is by using encryption and authentication techniques. Encryption transforms data into a form that cannot be read by unauthorized parties, while authentication ensures that only legitimate users can access the system. This research develops a network security system that implements encryption using the RSA (Rivest-Shamir-Adleman) algorithm and a two-factor authentication (2FA) mechanism. The results of the testing show that the combination of these two techniques significantly improves network security, reducing the potential for data breaches and unauthorized access. The system also facilitates the management of encryption keys and user verification processes. This study is expected to contribute to enhancing the resilience of network security, particularly in environments vulnerable to cyber threats.